Характеристика личности малолетнего преступника и причины её формирования - Vologdin E. V., Vologdina P. E. (Pedagogics and psychology: relevant theoretical and practical questions, 2016)
The article considers the question of the causes of a minor crime, it highlighted specific features, age characteristics of offenders in their teens, are some statistics on juvenile crime Altai region in comparison with the Russian Federation.
Keywords: преступность; инфантилизм; crime; нигилизм; juvenile delinquency; несовершеннолетняя преступность; the signs of a juvenile offender; a moral hedonism; conformity; moral autonomy; nihilism; infantilism; признаки несовершеннолетнего правонарушителя; моральный гедонизм; конформизм; моральная автономность